Self-assembly of semicrystalline PE-b-PS diblock copolymers within AAO nanoporous templates. (23rd July 2015) - Casas, María Teresa; Michell, Rose Mary; Blaszczyk-Lezak, Iwona; Puiggalí, Jordi; Mijangos, Carmen; Lorenzo, Arnaldo T.; Müller, Alejandro J.
Abstract: Strongly segregated polyethylene- b -polystyrene (PE- b -PS) diblock copolymers were infiltrated within anodic aluminum oxide nanoporous templates (AAO) (with 60 nm diameter). After carefully removing the nanofibers from the nanopores, TEM revealed their morphology. This is the first time that the morphology of semi-crystalline diblock copolymers infiltrated within AAO templates is observed. Regardless of their composition, the infiltrated nanofibers are constituted by core–shell or pseudo core–shell self-assembled nanocylinders. The affinity of PE to the AAO walls tailors the morphology towards PE shells with PS cores. The PS cores for some compositions have PE inclusions whose morphology is expected on the basis of previous computer simulation studies. Morphological observations successfully explain the confined crystallization of the PE block within the nanopores and the origin of novel double confinement effects (induced by glassy PS block and rigid AAO walls) on the PE block. Graphical abstract: Highlights: PS- b -PE strongly segregated diblock copolymers were infiltrated into nanoporous alumina. A method was developed to dissolve the alumina template and recover bundles of nanofibers. The nanofibers morphology was observed by TEM and successfully correlated with the crystallization behavior. The obtained morphologies can explain novel double confinement effects.